Legal Protection For Deep Vendors Procurement Of Government Goods And Services - Juwono, Stefanus Budi; Astutik, Sri; Cornelis, Vieta I (PT. Anagata Sembagi Education, 2025)
The procurement of goods/services for government purposes is one of the instruments driving the economy; therefore, budget absorption through procurement is crucial. However, no less important is the implementation of effective, efficient, and economical procurement to maximize the benefits of budget utilization. This research is normative and employs a statutory approach. The data analysis method used is descriptive qualitative, in which data is presented descriptively and analyzed qualitatively. This study focuses on legal protection for goods/services providers in procurement agreements. Such legal protection is regulated under Article 85 of Presidential Regulation No. 12 of 2021, which establishes mechanisms for contract dispute resolution through dispute resolution services, arbitration, the Construction Dispute Board, or court proceedings. In the era of Disruption 4.0 and the challenges of VUCA (Volatility, Uncertainty, Complexity, Ambiguity), the government encourages the involvement of the private sector and society through e-purchasing via electronic catalogs. E-procurement serves as a solution to improving the efficiency of national financial management. Disputes arising from defaults in government procurement of goods/services may result in administrative sanctions or civil lawsuits, as stipulated in Presidential Regulation No. 12 of 2021.